Cathode active material for lithium ion secondary battery, and lithium ion secondary battery
By using a specific proportion of lithium-nickel composite oxide positive electrode active material, the placeholding ratio of nickel in the crystal structure is controlled and a hexagonal layered structure is formed, which solves the problem of insufficient circulation performance of lithium-ion secondary batteries and achieves higher battery capacity and output performance.
Patent Information
- Application Number
- JP2023123250
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
AI Technical Summary
The existing lithium-ion secondary battery positive electrode active materials have shortcomings in circulation performance and need to be improved to improve their circulation characteristics.
A specific ratio of lithium-nickel composite oxide is used as the positive electrode active material. By controlling the molar ratio of lithium, nickel and other elements, and controlling the placeholding ratio of nickel in the crystal structure, a positive electrode active material with a hexagonal layered structure is formed. Nickel is used as a pillar between the crystal layers to stabilize the crystal structure and reduce the generation of lithium that does not participate in charge and discharge.
The circulation characteristics and battery capacity of lithium-ion secondary batteries are significantly improved, the reaction resistance is reduced, and the output performance of the battery is enhanced.
Smart Images

Figure 2025019575000002 
Figure 2025019575000003 
Figure 2025019575000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a lithium ion secondary battery and a lithium ion secondary battery. [Background technology]
[0002] In recent years, with the widespread use of portable electronic devices such as mobile phone terminals and notebook computers, there has been a strong demand for the development of small, lightweight non-aqueous electrolyte secondary batteries that have high energy density and durability. There has also been a strong demand for the development of high-output secondary batteries for use in power tools and electric vehicles, including hybrid vehicles.
[0003] Non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries are available as secondary batteries that meet these requirements. Lithium ion secondary batteries, which use lithium metal composite oxides with layered or spinel-type crystal structures as the positive electrode active material, can obtain high voltages of about 4V, and are therefore being put to practical use as batteries with high energy density.
[0004] Lithium metal composite oxides include lithium cobalt composite oxide (LiCoO2), which is relatively easy to synthesize, lithium nickel composite oxide (LiNiO2), which uses nickel, which is cheaper than cobalt, and lithium nickel cobalt manganese composite oxide (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), lithium manganese composite oxide (LiMn2O4), lithium nickel manganese composite oxide (LiNi 0.5 Mn 0.5 O2) have been proposed.
[0005] In recent years, there has been a demand for further improvements in the battery characteristics of lithium-ion secondary batteries, and various studies have been conducted.
[0006] For example, Patent Documents 1 to 5 disclose that by controlling the particle characteristics of a lithium composite oxide, it is possible to improve the cycle characteristics, which is the capacity retention rate when repeatedly charged and discharged, of a lithium ion secondary battery using the lithium composite oxide. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2001-243949 A [Patent Document 2] JP 2004-355824 A [Patent Document 3] JP 2017-188444 A [Patent Document 4] JP 2017-188445 A [Patent Document 5] International Publication No. 2017 / 169129 Summary of the Invention [Problem to be solved by the invention]
[0008] However, as described above, lithium ion secondary batteries are being used in various applications, and further improvements in performance are being demanded. For this reason, there is also a demand for improving the performance, such as cycle characteristics, of positive electrode active materials for lithium ion secondary batteries when used in lithium ion secondary batteries by a method different from the conventional method.
[0009] In view of the problems associated with the above-mentioned conventional techniques, an object of one aspect of the present invention is to provide a positive electrode active material for lithium ion secondary batteries that has excellent cycle characteristics when used in lithium ion secondary batteries. [Means for solving the problem]
[0010] In order to solve the above problem, according to one aspect of the present invention, A positive electrode active material for a lithium ion secondary battery containing a lithium nickel composite oxide having a hexagonal layered structure, The lithium nickel composite oxide contains lithium (Li), nickel (Ni), and element M (M) in a molar ratio of Li:Ni:M = a:b:c (where 0.90 ≦ a < 1.00, 0.80 ≦ b < 1.00, 0.00 < c ≦ 0.20, b + c = 1, and the element M is at least one element selected from the group consisting of Mn, Co, Al, Ti, Zr, W, Fe, Si, Nb, Mg, Ca, B, Na, K, Mo, Cu, V, P, and Ba), Provided is a positive electrode active material for a lithium ion secondary battery, in which the occupancy of nickel in the lithium site (3b site) obtained by analyzing the powder neutron diffraction pattern of the lithium nickel composite oxide by the Rietveld method is 2.5% or more and 10.0% or less.
Advantages of the Invention
[0011] According to one aspect of the present invention, when used in a lithium ion secondary battery, a positive electrode active material for a lithium ion secondary battery having excellent cycle characteristics can be provided.
Brief Description of the Drawings
[0012] [Figure 1] FIG. 1 is a flow chart of a method for manufacturing a positive electrode active material. [Diagram 2] FIG. 2 is a schematic explanatory diagram of a coin-type battery used for battery evaluation. [Diagram 3] FIG. 3 is a schematic explanatory diagram of a laminate-type battery used for battery evaluation. [Figure 4] FIG. 4 is a powder neutron diffraction pattern of the lithium nickel composite oxide obtained in Example 2 and a simulation pattern by Rietveld analysis.
Embodiments for Carrying Out the Invention
[0013] Hereinafter, the form for carrying out the present invention will be described with reference to the drawings. However, the present invention is not limited to the following embodiment, and various modifications and substitutions can be made to the following embodiment without departing from the scope of the present invention. [Positive electrode active material for lithium-ion secondary batteries] Hereinafter, the positive electrode active material for a lithium ion secondary battery (hereinafter, also simply referred to as "positive electrode active material") of this embodiment will be described. (1) Lithium nickel composite oxide The positive electrode active material of the present embodiment contains a lithium nickel composite oxide. The positive electrode active material of the present embodiment may be composed only of a lithium nickel composite oxide, but even in this case, it does not exclude the inclusion of inevitable impurities that are mixed in during the manufacturing process or the like.
[0014] The lithium nickel composite oxide can have a hexagonal layered structure. (1-1) Particle morphology The form of the lithium nickel composite oxide particles is not particularly limited. For example, the lithium nickel composite oxide may contain at least one of a single primary particle and a secondary particle formed by agglomeration of a plurality of primary particles. Therefore, the lithium nickel composite oxide may contain both a single primary particle and the above-mentioned secondary particles. The lithium nickel composite oxide may be composed of only a single primary particle or only secondary particles.
[0015] Whether the lithium nickel composite oxide particles contain primary particles, secondary particles, or both can be roughly confirmed by scanning electron microscope (SEM) observation images (hereinafter also referred to as "SEM images") of the particles, but this may lack accuracy. In the positive electrode active material according to this embodiment, it is preferable to process the cross section of the particles and use the SEM images to determine the presence or absence of primary particles and secondary particles.
[0016] Specifically, for example, a lithium nickel composite oxide is embedded in a resin, and after being processed by a cross-section polisher (CP) or the like to enable cross-sectional observation of the particles, SEM images are observed to determine the presence or absence of primary particles and secondary particles. For the determination, it is preferable to perform the above evaluation on 50 or more particles. The upper limit of the number of particles to be evaluated is not particularly limited, but considering the productivity of the evaluation, it is preferable to evaluate 200 or fewer particles.
[0017] In addition, when using the band contrast of the electron backscatter diffraction (hereinafter also referred to as "EBSD") method or a focused ion beam (FIB) processing apparatus during cross-section processing, the cross-section of the above particles can also be confirmed using the attached scanning ion microscope (SIM) observation image. (1-2) Constituent elements The lithium nickel composite oxide contains lithium (Li), nickel (Ni), and element M (M). Examples of element M include at least one element selected from the group consisting of Mn, Co, Al, Ti, Zr, W, Fe, Si, Nb, Mg, Ca, B, Na, K, Mo, Cu, V, P, and Ba. In addition, a small amount of elements other than the above elements may be contained.
[0018] The lithium nickel composite oxide can contain lithium (Li), nickel (Ni), and element M (M), which are elements excluding oxygen, in a molar ratio of Li:Ni:M = a:b:c.
[0019] The above a, b, and c satisfy 0.90 ≦ a < 1.00, 0.80 ≦ b < 1.00, 0.00 < c ≦ 0.20, and b + c = 1.
[0020] Note that the lithium nickel composite oxide can be represented as Li a Ni b M c O 2+α where α preferably satisfies -0.2 ≦ α ≦ 0.2. Since a, b, c, and element M have been described above, the description is omitted.
[0021] The following describes each element. (Lithium) In the above ratio of the amounts of substances, the value of a indicating the molar ratio of Li corresponds to the molar ratio of lithium (Li) to an element (Me) other than lithium and oxygen (Li / Me ratio). The element (Me) other than lithium and oxygen corresponds to Ni and element M. In the above ratio of the amounts of substances, the range of a is 0.90 ≦ a < 1.00. That is, it is preferable that lithium is deficient compared to the case where a = 1.00 which is the stoichiometric ratio of the lithium nickel composite oxide.
[0022] By setting the value of a to 0.90 or more, the reaction resistance can be suppressed and the output of the battery can be increased. By setting the value of a to less than 1.00, the amount of the lithium compound attached to the particle surface of the positive electrode active material of the present embodiment, that is, the amount of alkali can be suppressed. Therefore, when the positive electrode active material of the present embodiment is applied to a lithium ion secondary battery (hereinafter also referred to as "secondary battery"), gas generation during the battery reaction can be suppressed.
[0023] Preferably, a is 0.92 ≦ a < 0.99. (Nickel) In the above ratio of the amounts of substances, the range of b indicating the molar ratio of Ni is 0.80 ≦ b < 1.00. When the value of b is within the above range, when the positive electrode active material of the present embodiment is applied to a secondary battery, it can have a high battery capacity. (Element M) In the above ratio of the amounts of substances, the range of c indicating the molar ratio of element M is 0.00 < c ≦ 0.20, preferably 0.02 ≦ c ≦ 0.20, and more preferably 0.05 ≦ c ≦ 0.20. Note that the lithium nickel composite oxide may contain a plurality of types of element M. In this case, it is preferable that the total molar ratio of element M contained in the lithium nickel composite oxide satisfies the above range. Since the candidate elements of element M have been described above, the description is omitted. The type of element M contained in the lithium nickel composite oxide can be appropriately selected according to required battery characteristics and the like.
[0024] For example, element M may contain Co. When the molar ratio of Co contained in c of the above molar ratio is defined as c1, the range of c1 is preferably 0 < c1 ≤ 0.20, more preferably 0.02 ≤ c1 ≤ 0.18, and even more preferably 0.03 ≤ c1 ≤ 0.15. When the value of c1 is within the above range, when the cathode active material of the present embodiment is applied to a secondary battery, high thermal stability and output characteristics can be exhibited. When element M contains only Co, c = c1. Also, as described above, it is preferable that the total molar amount of element M satisfies the range of c described above. Therefore, for example, c1 + c2 + c3, which is the sum of c2 and c3 described below, preferably satisfies the suitable range of c described above.
[0025] Also, element M may contain Mn. When the molar ratio of Mn contained in c of the above molar ratio is defined as c2, the range of c2 is preferably 0 < c2 ≤ 0.20, more preferably 0.02 ≤ c2 ≤ 0.20, and even more preferably 0.05 ≤ c2 ≤ 0.20. When the range of c2 is within the above range, when the cathode active material of the present embodiment is applied to a secondary battery, the thermal stability can be enhanced. When element M contains only Mn, c = c2.
[0026] Element M may contain Al. When the molar ratio of Al contained in c of the above molar ratio is defined as c3, the range of c3 is preferably 0 < c3 ≤ 0.10, more preferably 0.01 ≤ c3 ≤ 0.08, and even more preferably 0.01 ≤ c3 ≤ 0.06. When the range of c3 is within the above range, when the cathode active material of the present embodiment is applied to a secondary battery, the thermal stability can be enhanced. When element M contains only Al, c = c3.
[0027] Note that the composition of the lithium nickel composite oxide can be measured by quantitative analysis using inductively coupled plasma (ICP) optical emission spectrometry. (1-3) Occupancy of nickel at the lithium site (3b site) In the lithium nickel composite oxide contained in the positive electrode active material according to this embodiment, the occupancy rate of nickel (Ni) in the lithium sites (3b sites), which is obtained by analyzing a powder neutron diffraction pattern measured by powder neutron diffraction using the Rietveld method, is preferably 2.5% or more and 10.0% or less, more preferably 2.6% or more and 8.0% or less, even more preferably 2.7% or more and 7.0% or less, and particularly preferably more than 2.9% and 7.0% or less.
[0028] The occupancy rate of nickel in the lithium site (3b site) determined from the above powder neutron diffraction pattern is hereinafter also referred to as "Ni(Li(3b))".
[0029] When a secondary battery is repeatedly charged and discharged, lithium is repeatedly inserted and removed between the layers of the lithium nickel composite oxide. However, when a secondary battery is repeatedly charged and discharged, the space between the layers repeatedly expands and contracts as lithium is inserted and removed, causing the crystal structure of the lithium nickel composite oxide to change, resulting in lithium that does not contribute to charging and discharging. This is thought to result in a decrease in cycle characteristics.
[0030] In contrast, in the lithium nickel composite oxide contained in the positive electrode active material of this embodiment, nickel occupies a part of the lithium site. Therefore, even when lithium is removed from between the layers of the lithium nickel composite oxide, nickel remains between the layers. That is, it is considered that the nickel functions as a pillar between the layers and can suppress the change in the interlayer distance when the secondary battery is repeatedly charged and discharged. Therefore, even when the secondary battery is repeatedly charged and discharged, the change in the crystal structure of the lithium nickel composite oxide can be suppressed, and the generation of lithium that does not contribute to charging and discharging can be suppressed. Therefore, according to the positive electrode active material of this embodiment, it is possible to improve the cycle characteristics when used in a secondary battery by a method that has not been used in the past, which is to control the occupancy rate of nickel in the lithium site.
[0031] Specifically, by making the Ni(Li(3b)) 2.5% or more, it is believed that the nickel can fully function as an interlayer pillar, stabilizing the crystal structure during charging and discharging, and particularly improving the cycle characteristics. In addition, by making the Ni(Li(3b)) 10.0% or less, it is possible to suppress the deterioration of the crystal integrity of the lithium nickel composite oxide. As a result, it is possible to ensure a sufficient amount of lithium that contributes to charging and discharging, suppress reaction resistance, and sufficiently increase battery capacity and output.
[0032] In addition, when calculating the Ni(Li(3b)), it is also possible to use an X-ray diffraction pattern in the Rietveld analysis. However, the lithium nickel composite oxide contained in the positive electrode active material of this embodiment can contain, in addition to nickel, an element M, such as cobalt or manganese, which is difficult to identify with X-rays. In addition, it is difficult to accurately evaluate light elements such as lithium, hydrogen, and oxygen with X-rays. For this reason, when using an X-ray diffraction pattern, it is generally difficult to calculate an accurate value of Ni(Li(3b)).
[0033] In contrast, by using neutron beams, the elements contained in the lithium nickel composite oxide can be evaluated more accurately than when using X-ray diffraction patterns. Therefore, when calculating the Ni(Li(3b)), it is necessary to use a powder neutron diffraction pattern. (1-4)(003) peak half-width The lithium nickel composite oxide contained in the positive electrode active material of this embodiment has a diffraction peak assigned to the (003) plane in a powder X-ray diffraction pattern measured by powder X-ray diffraction method (hereinafter also referred to as "XRD") using Cu-Kα radiation as an X-ray source. The lithium nickel composite oxide contained in the positive electrode active material of this embodiment preferably has a half-width value of the diffraction peak of the (003) plane in the X-ray diffraction pattern of 0.074° or more and 0.125° or less. The half-width of the diffraction peak of the (003) plane means the width of the profile at half the intensity value of the diffraction peak assigned to the (003) plane.
[0034] The half-width of the diffraction peak of the (003) plane is an index for grasping the crystallinity and the primary particle size of the lithium nickel composite oxide. By setting the half-width of the diffraction peak of the (003) plane to 0.125° or less, the lithium nickel composite oxide can be made to have particularly excellent crystallinity. In addition, the size of the primary particles is suitable for improving cycle characteristics. Therefore, when the positive electrode active material of this embodiment containing the lithium nickel composite oxide is applied to a secondary battery, the battery capacity and capacity retention rate can be particularly increased, and a secondary battery with particularly excellent battery capacity and cycle characteristics can be obtained. However, even if the half-width of the diffraction peak of the (003) plane is excessively small, the effect of increasing the battery capacity and capacity retention rate is saturated, so that the half-width of the diffraction peak of the (003) plane is preferably 0.074° or more.
[0035] The X-ray diffraction pattern is preferably measured using an XRD diffractometer equipped with a Bragg-Brentano optical system and a flat sample holder. (1-5) Median diameter (D50) The median diameter (D50) in the volume-based particle size distribution of the positive electrode active material according to this embodiment measured by a laser diffraction / scattering method is preferably 0.1 μm or more and 20.0 μm or less, more preferably 1.0 μm or more and 18.0 μm or less, and even more preferably 2.0 μm or more and 17.0 μm or less.
[0036] By making the median diameter of the positive electrode active material of this embodiment 20.0 μm or less, the contact area with the electrolyte can be sufficiently increased when applied to a secondary battery, thereby increasing the battery capacity. Also, by making the median diameter of the positive electrode active material of this embodiment 0.1 μm or more, the handling property during electrode preparation can be improved.
[0037] The median diameter (D50) can be determined, for example, from a volume integrated value measured by a laser light diffraction scattering type particle size distribution analyzer. (1-6) Average primary particle diameter The average primary particle size of the lithium nickel composite oxide is preferably 0.05 μm or more and 1.0 μm or less. By making the average primary particle size of the lithium nickel composite oxide 0.05 μm or more, it means that the size of the primary particles and the crystallites constituting the primary particles can be sufficiently large, and the crystallinity of the lithium nickel composite oxide can be improved. Therefore, when the positive electrode active material of this embodiment containing the lithium nickel composite oxide is applied to a secondary battery, the battery capacity can be increased, and a secondary battery excellent in battery capacity and cycle characteristics can be obtained.
[0038] However, even if the average primary particle size of the lithium nickel composite oxide is excessively large, the effect of increasing the battery capacity is saturated, so the average primary particle size of the lithium nickel composite oxide is preferably 1.0 μm or less.
[0039] The average primary particle size of the lithium nickel composite oxide is determined by selecting primary particles of the lithium nickel composite oxide that can be observed in their entirety by a scanning electron microscope (SEM), measuring their major axis lengths, and averaging them. When calculating the average primary particle size, the number of primary particles to be evaluated is not particularly limited.
[0040] For example, when the lithium nickel composite oxide contains secondary particles, it is preferable to select a total of 20 to 30 primary particles from each of 10 to 20 secondary particles, and measure the major axis length of the selected primary particles.
[0041] In addition, when the lithium nickel composite oxide contains a single primary particle that does not constitute a secondary particle, it is preferable to evaluate 5 or more primary particles of the lithium nickel composite oxide. There is no particular upper limit on the number of primary particles to be evaluated, but it is preferable to evaluate, for example, 20 or less.
[0042] When the lithium nickel composite oxide contains only secondary particles or only single primary particles, the above number of primary particles can be selected for the secondary particles or single primary particles. The lengths of the major axes of the selected primary particles can then be measured, and the average value can be regarded as the average primary particle size of the lithium nickel composite oxide.
[0043] When the lithium nickel composite oxide contains both secondary particles and single primary particles, the above-mentioned number of primary particles can be selected for each of the secondary particles and the single primary particles. The major axis lengths of all the selected primary particles are then measured, and the average value thereof can be regarded as the average primary particle size of the lithium nickel composite oxide.
[0044] By setting the median diameter (D50) of the positive electrode active material in the above-mentioned range and setting the average primary particle diameter of the contained lithium nickel composite oxide in the above-mentioned range, when the positive electrode active material is applied to a secondary battery, it is possible to particularly increase the battery capacity and cycle characteristics, and to achieve both. (1-7) Amount of dissolved lithium From the viewpoint of suppressing gas generation in a secondary battery, in the positive electrode active material of this embodiment, the amount of lithium eluted into water when the positive electrode active material is immersed in water (hereinafter also referred to as "amount of eluted lithium") is preferably 0.15 mass % or less, and more preferably 0.10 mass % or less, with respect to the entire positive electrode active material.
[0045] By setting the amount of eluted lithium within the above range, gas generation in the secondary battery can be suppressed.
[0046] The lower limit of the amount of eluted lithium from the positive electrode active material of this embodiment is not particularly limited, but is preferably, for example, 0.05 mass % or more.
[0047] When it is particularly necessary to suppress the amount of eluted lithium in the positive electrode active material, the lithium nickel composite oxide preferably contains Zr as the element M. In addition, the amount of eluted lithium can also be suppressed by performing a water washing treatment on the positive electrode active material. [Method of manufacturing positive electrode active material for lithium ion secondary batteries] The method for producing the positive electrode active material for a lithium ion secondary battery is not particularly limited as long as the positive electrode active material having the above characteristics can be obtained. Hereinafter, an example of the method for producing the positive electrode active material according to the present embodiment will be described.
[0048] As described above, according to the method for producing a positive electrode active material of this embodiment, the positive electrode active material already described can be produced, and therefore some of the matters already described will not be described again.
[0049] The method for producing a positive electrode active material of this embodiment can be carried out, for example, according to flow 10 shown in Fig. 1. That is, the method for producing a positive electrode active material of this embodiment can include a mixing step (S1) and a firing step (S2).
[0050] In the mixing step (S1), a nickel composite compound and a lithium compound are mixed to obtain a raw material mixture.
[0051] In the calcination step (S2), the raw material mixture is calcined to produce a lithium nickel composite oxide.
[0052] In addition, the element M may be added as a compound of the element M separately from the nickel composite compound in the mixing step (S1), or may be added by using a nickel composite compound containing the element M.
[0053] An example of the configuration of each step will be described below. (1) Mixing process (S1) In the mixing step (S1), the nickel composite compound and the lithium compound are mixed together to obtain a raw material mixture, as described above. In addition, in the mixing step, a compound of element M can also be added and mixed, if necessary.
[0054] The nickel composite compound, the lithium compound, and the compound of element M added as needed can be added, for example, in the form of powder (solid phase) and mixed. Hereinafter, each material, which is the raw material provided to the mixing step, will be described. (1-1) Raw materials (Nickel complex compound) The nickel composite compound used in the mixing step (S1) can be obtained by a known method. The content ratio (composition ratio), which is the substance amount ratio between Ni, which is an element in the nickel composite compound, and element M, such as Co, is almost maintained in the lithium nickel composite oxide particles. For this reason, the content ratio of each element is preferably in the same range as the content ratio in the above-mentioned lithium nickel composite oxide. For this reason, the nickel composite compound preferably contains nickel (Ni) and element M (M) in a substance amount ratio of Ni:M=b:c. Since b, c, and element M have been explained in the lithium nickel composite oxide, explanations will be omitted.
[0055] The nickel composite compound used in this embodiment may contain small amounts of elements other than the above-mentioned elements (element M such as Ni or Co) and oxygen, as long as the effects of the present invention are not impaired.
[0056] The nickel composite compound may be a hydroxide or an oxide. It may also be a mixture of a hydroxide and an oxide. Examples of a method for producing a nickel composite hydroxide include a method of neutralization and crystallization using an aqueous solution of a metal salt and an alkaline solution. In addition, a part or all of the nickel composite hydroxide may be converted into a nickel composite oxide by, for example, heat-treating the nickel composite hydroxide to remove moisture from the nickel composite hydroxide.
[0057] In addition, when the nickel composite compound is a nickel composite hydroxide, Ni b M c (OH) 2+β In addition, when the nickel composite compound is a nickel composite oxide, Ni b M c O 1+γ It is preferable that b, c, and element M are the same as those described for the lithium nickel composite oxide, and therefore the description thereof will be omitted. It is preferable that β and γ satisfy −0.2≦β≦0.2 and −0.2≦γ≦0.2, respectively. (Lithium compounds) The lithium compound is not particularly limited, and any known compound containing lithium can be used, for example, one or more selected from lithium carbonate, lithium hydroxide, and lithium nitrate. The lithium compound may be a mixture of two or more compounds selected from the above compounds.
[0058] The lithium compound is preferably one or more selected from lithium carbonate and lithium hydroxide from the viewpoints of being less affected by residual impurities and dissolving at the firing temperature, and is more preferably lithium hydroxide from the viewpoint of obtaining a lithium nickel composite oxide having particularly high crystallinity. (Compound of element M) As described above, in the mixing step, a compound of element M can be added and mixed as necessary. The type of compound of element M is not particularly limited, but it is preferable to use one or more types selected from hydroxides, oxides, chlorides, nitrates, sulfates, carbonates, etc. (1-2) Mixing method There is no particular limitation on the method of mixing the nickel composite compound, the lithium compound, and the compound of element M that is added as necessary. It is preferable to mix these particles sufficiently without destroying their shells.
[0059] The raw materials such as nickel composite compound can be mixed using, for example, a general mixer, such as a shaker mixer, a Loedige mixer, a Julia mixer, or a V blender. If the mixing is insufficient, the mass ratio (Li / Me) of lithium (Li) and elements other than lithium and oxygen (Me) may vary between individual particles of the positive electrode active material, resulting in problems such as insufficient battery characteristics. As mentioned above, the elements other than lithium and oxygen (Me) correspond to Ni and element M. (1-3) Mixing ratio The lithium compounds are preferably mixed so that the Li / Me ratio in the mixture obtained in the mixing step is 0.90 or more and less than 1.00. In other words, it is preferable to mix so that the Li / Me ratio in the raw material mixture is the same as the Li / Me ratio in the resulting fired product. This is because the Li / Me ratio and the ratio of the amounts of substances of each element for lithium, nickel, and element M do not change before and after the firing step (S2), so the Li / Me ratio in the raw material mixture in the mixing step (S1) becomes equal to the Li / Me ratio in the fired product. The content (ratio) of the elements in the raw material mixture is almost maintained in the lithium nickel composite oxide. (2) Firing process (S2) The firing step (S2) is a step of firing the raw material mixture obtained in the mixing step (S1) to obtain a fired product containing a lithium nickel composite oxide. When the raw material mixture is fired, the lithium in the lithium compound diffuses into the nickel composite compound to form a lithium nickel composite oxide. The lithium compound melts at the firing temperature and permeates into the nickel composite compound to form a fired product of the lithium nickel composite oxide.
[0060] The firing conditions in the firing step (S2) are not particularly limited, and can be selected so that the lithium nickel composite oxide has a desired composition and the properties such as the nickel occupancy rate of the lithium site (3b site) are within the desired range. Preferred examples of the firing conditions are described below. (atmosphere) The firing atmosphere is preferably an oxidizing atmosphere. The oxidizing atmosphere preferably has an oxygen concentration of 80% by volume or more, more preferably an oxygen concentration of 85% by volume or more. The oxidizing atmosphere can also be an oxygen atmosphere, so the oxygen concentration can be 100% by volume or less. (Firing temperature) It is preferable to perform the firing in two steps, that is, to raise the temperature to the first firing temperature and hold it there (first firing step), then raise the temperature to the second firing temperature and hold it there (second firing step), and then cool it.
[0061] For example, the first firing temperature, which is the temperature for the first stage of firing, is preferably 400° C. or higher and 600° C. or lower, and the holding time at the first firing temperature is preferably 5 hours or longer.
[0062] The second firing temperature, which is the second stage firing temperature, is preferably 600° C. or higher and 770° C. or lower, and the holding time at the second firing temperature is preferably 10 hours or longer. The second firing temperature is preferably higher than the first firing temperature.
[0063] When calcining with the above temperature pattern, the lithium nickel composite oxide has high crystallinity even in a state where Li is deficient compared to the stoichiometric ratio, and a positive electrode active material with high battery capacity can be obtained. In addition, the occupancy rate of nickel in the lithium site (3b site) can be easily set within the above-mentioned range. Note that, depending on the lithium and nickel content in the target composition of the lithium nickel composite oxide, the calcination conditions such as a suitable calcination temperature may change in order to set the occupancy rate of nickel in the lithium site (3b site) in the desired range. For this reason, it is preferable to select the optimal calcination temperature within the above temperature range according to the target composition, and to select temperature conditions such as the heating rate and holding time.
[0064] When a two-stage firing process is performed, in the first firing process, which is a first-stage firing process at a first firing temperature, the lithium compound is melted and sufficiently diffused into the nickel composite compound, so that the lithium and the nickel composite compound can react with each other. Then, in the second firing process, which is a second-stage firing process at a second firing temperature, crystal growth can be promoted.
[0065] The method for producing a positive electrode active material according to the present embodiment may include any step other than the mixing step and the firing step. (3) Crushing process The fired product obtained in the firing step (S2) can also be used as the positive electrode active material of this embodiment. However, the fired product obtained after the firing step (S2) may have coarse particles formed due to weak sintering or aggregation, although sintering between particles is suppressed. In such a case, the method for producing the positive electrode active material of this embodiment can also include a crushing step of crushing the fired product. By crushing the fired product, the sintering and aggregation can be eliminated, and the particle size distribution can be adjusted. (4) Crushing process The method for producing a positive electrode active material of this embodiment may also include a pulverization step of pulverizing the sintered product or the pulverized powder after the sintering step (S2) or after the above-mentioned pulverization step.
[0066] By including a pulverization step in the method for producing a positive electrode active material according to the present embodiment, secondary particles can be converted into primary particles, and a lithium nickel composite oxide mainly composed of primary particles can be obtained.
[0067] The primary particles obtained after the pulverization step may be used alone or in combination with agglomerated particles.
[0068] After the crushing or pulverizing step, sieving may be carried out to select particles of a desired particle size. (5)Water washing process The method for producing a positive electrode active material of this embodiment may also include a water washing step of washing the fired product obtained in the firing step (S2) with water.
[0069] By carrying out the water washing step, excess lithium remaining on the particle surfaces of the lithium nickel composite oxide can be removed.
[0070] In the water-washing step, the fired product can be mixed with water to form a slurry and then washed with water (slurrying step).
[0071] The water used in forming a slurry in the water washing step is not particularly limited, but for example, it is preferable to use water having an electrical conductivity of less than 10 μS / cm, and more preferably water having an electrical conductivity of 1 μS / cm or less.
[0072] It is preferable to stir the prepared slurry during washing with water.
[0073] In the water washing step, after the slurry is made, the slurry is subjected to solid-liquid separation, i.e., filtration and dehydration to obtain water-washed powder (solid-liquid separation step). The apparatus used for filtration and dehydration is not particularly limited, and for example, a centrifugal separation type or a filter press type solid-liquid separation apparatus can be used.
[0074] In the water washing step, the water-washed powder containing water obtained after solid-liquid separation is preferably dried (drying step). The drying conditions are not particularly limited, but it is preferable to perform the drying at a temperature of 100° C. or higher and 350° C. or lower in an oxidizing atmosphere or a vacuum atmosphere.
[0075] In the mixing step, a lithium nickel composite oxide having a Li / Me of 0.90 or more and less than 1.00 can be obtained by washing the fired product of the lithium nickel composite oxide produced under the above-mentioned conditions of Li / Me of 1.00 or more with water. However, according to the investigations of the inventors of the present invention, in the above case, a positive electrode active material that satisfies the requirements of the positive electrode active material of this embodiment in terms of the nickel occupancy rate of the lithium site (3b site) and the like cannot be obtained, and the effects of the positive electrode active material of this embodiment cannot be obtained. [Lithium-ion secondary battery] The lithium ion secondary battery of this embodiment includes at least a positive electrode, a negative electrode, and a non-aqueous electrolyte, and the positive electrode can include the above-described positive electrode active material for lithium ion secondary batteries.
[0076] Hereinafter, one configuration example of the secondary battery of this embodiment will be described for each component. The secondary battery of this embodiment includes, for example, a positive electrode, a negative electrode, and a non-aqueous electrolyte, and is composed of the same components as a general lithium-ion secondary battery. Note that the embodiment described below is merely an example, and the lithium-ion secondary battery of this embodiment can be embodied in various forms that have been modified and improved based on the knowledge of those skilled in the art, including the following embodiment. In addition, the secondary battery is not particularly limited in its use. (positive electrode) The positive electrode of the secondary battery of this embodiment can contain the positive electrode active material described above.
[0077] An example of a method for manufacturing a positive electrode is described below. First, the positive electrode active material (powder), conductive material, and binder are mixed to prepare a positive electrode mixture, and activated carbon and a solvent for viscosity adjustment, etc. are added as necessary, and the mixture is kneaded to prepare a positive electrode mixture paste.
[0078] The mixing ratio of each material in the positive electrode mixture is a factor that determines the performance of the lithium ion secondary battery, and can be adjusted depending on the application. The mixing ratio of the materials can be the same as that of the positive electrode of a known lithium ion secondary battery, and for example, when the total mass of the solid content of the positive electrode mixture excluding the solvent is 100 mass%, the positive electrode active material can be contained in a ratio of 60 mass% to 95 mass%, the conductive material can be contained in a ratio of 1 mass% to 20 mass%, and the binder can be contained in a ratio of 1 mass% to 20 mass%.
[0079] The obtained positive electrode composite paste is applied to the surface of a current collector made of, for example, aluminum foil, and dried to remove the solvent, thereby producing a sheet-like positive electrode. If necessary, pressure can be applied by a roll press or the like to increase the electrode density. The sheet-like positive electrode thus obtained can be cut to an appropriate size according to the desired battery and used for the production of the battery.
[0080] As the conductive material, for example, graphite (natural graphite, artificial graphite, expanded graphite, etc.) and carbon black-based materials such as acetylene black and Ketjen Black (registered trademark) can be used.
[0081] The binder serves to bind the active material particles together, and may be, for example, one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose-based resin, polyacrylic acid, etc.
[0082] If necessary, a solvent for dispersing the positive electrode active material, conductive material, etc. and dissolving the binder can be added to the positive electrode mixture. Specifically, an organic solvent such as N-methyl-2-pyrrolidone can be used as the solvent. Activated carbon can also be added to the positive electrode mixture to increase the electric double layer capacity.
[0083] The method for producing the positive electrode is not limited to the above-mentioned example, and other methods may be used. For example, the positive electrode may be produced by pressing a positive electrode mixture and then drying it in a vacuum atmosphere. (Negative electrode) The negative electrode may be made of metallic lithium, a lithium alloy, etc. Alternatively, the negative electrode may be made by mixing a binder with a negative electrode active material capable of absorbing and desorbing lithium ions, adding an appropriate solvent to make a paste-like negative electrode mixture, applying the paste to the surface of a metal foil current collector such as copper, drying it, and compressing it to increase the electrode density as necessary.
[0084] As the negative electrode active material, for example, natural graphite, artificial graphite, sintered organic compounds such as phenol resin, and powder of carbon material such as coke can be used. In this case, as with the positive electrode, fluorine-containing resin such as PVDF can be used as the negative electrode binder, and an organic solvent such as N-methyl-2-pyrrolidone can be used as the solvent for dispersing these active materials and binders. (Separator) A separator may be sandwiched between the positive electrode and the negative electrode as necessary. The separator separates the positive electrode and the negative electrode and holds the electrolyte, and any known separator may be used, such as a thin membrane made of polyethylene or polypropylene having many minute pores. (Non-aqueous electrolyte) As the non-aqueous electrolyte, for example, a non-aqueous electrolytic solution can be used.
[0085] As the non-aqueous electrolyte, for example, a solution in which a lithium salt as a supporting salt is dissolved in an organic solvent can be used. Alternatively, as the non-aqueous electrolyte, a solution in which a lithium salt is dissolved in an ionic liquid can be used. Note that the ionic liquid refers to a salt that is composed of cations and anions other than lithium ions and is liquid even at room temperature.
[0086] The organic solvent may be one selected from cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and trifluoropropylene carbonate; chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and dipropyl carbonate; ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, and dimethoxyethane; sulfur compounds such as ethyl methyl sulfone and butane sultone; and phosphorus compounds such as triethyl phosphate and trioctyl phosphate. Two or more of these organic solvents may be used in combination.
[0087] The supporting salt may be LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, or a composite salt thereof. Furthermore, the non-aqueous electrolyte may contain a radical scavenger, a surfactant, a flame retardant, and the like.
[0088] The non-aqueous electrolyte may be a solid electrolyte. The solid electrolyte has a property of being able to withstand high voltage. Examples of the solid electrolyte include inorganic solid electrolytes and organic solid electrolytes.
[0089] Examples of the inorganic solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes.
[0090] The oxide-based solid electrolyte is not particularly limited, and for example, an oxide-based solid electrolyte containing oxygen (O) and having lithium ion conductivity and electronic insulation can be suitably used. Examples of the oxide-based solid electrolyte include lithium phosphate (Li3PO4), Li3PO4N X , LiBON X, LiNbO3, LiTaO3, Li2SiO3, Li4SiO4-Li3PO4, Li4SiO4-Li3VO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3-ZnO, Li 1+X Al X Ti 2-X (PO4)3(0≦X≦1), Li 1+X Al X Ge 2-X (PO4)3(0≦X≦1), LiTi2(PO4)3, Li 3X La 2 / 3-X TiO3(0≦X≦2 / 3), Li5La3Ta2O 12 , Li7La3Zr2O 12 , Li6BaLa2Ta2O 12 , Li 3.6 S 0.6 P 0.4 One or more types selected from O4, etc. can be used.
[0091] The sulfide-based solid electrolyte is not particularly limited, and for example, one containing sulfur (S) and having lithium ion conductivity and electronic insulation can be suitably used. For example, the sulfide-based solid electrolyte can be one or more selected from Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, etc.
[0092] As the inorganic solid electrolyte, materials other than those mentioned above may be used, for example, Li3N, LiI, Li3N-LiI-LiOH, etc. may be used.
[0093] The organic solid electrolyte is not particularly limited as long as it is a polymer compound exhibiting ion conductivity, and examples of the organic solid electrolyte that can be used include polyethylene oxide, polypropylene oxide, copolymers thereof, etc. The organic solid electrolyte may also contain a supporting salt (lithium salt). (Shape and structure of secondary battery) The lithium ion secondary battery of the present embodiment described above can be made into various shapes such as a cylindrical shape, a laminated shape, etc. Regardless of the shape, if the secondary battery of the present embodiment uses a non-aqueous electrolyte solution as the non-aqueous electrolyte, the positive electrode and the negative electrode are laminated via a separator to form an electrode body, the obtained electrode body is impregnated with a non-aqueous electrolyte solution, and the positive electrode current collector and the positive electrode terminal connected to the outside, and the negative electrode current collector and the negative electrode terminal connected to the outside are connected using a current collecting lead or the like, and the battery case is sealed to form a structure.
[0094] As described above, the secondary battery of the present embodiment is not limited to a form using a non-aqueous electrolyte solution as a non-aqueous electrolyte, and may be, for example, a secondary battery using a solid non-aqueous electrolyte, i.e., an all-solid-state battery. When making an all-solid-state battery, the configuration other than the positive electrode active material may be changed as necessary.
[0095] The secondary battery of this embodiment can be used for various purposes. Since the secondary battery of this embodiment can be a high-capacity, high-output secondary battery, it is suitable for use as a power source for small portable electronic devices (such as notebook personal computers and mobile phone terminals) that always require high capacity, and is also suitable as a power source for electric vehicles that require high output.
[0096] In addition, the secondary battery of this embodiment can be made compact and have high output, making it suitable as a power source for electric vehicles that are limited in installation space. The secondary battery of this embodiment can be used not only as a power source for electric vehicles that are driven purely by electrical energy, but also as a power source for so-called hybrid vehicles that are used in conjunction with combustion engines such as gasoline engines and diesel engines. EXAMPLES
[0097] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0098] First, the evaluation methods of the positive electrode active materials and secondary batteries obtained in the following Examples and Comparative Examples will be described. (Evaluation of Positive Electrode Active Material) The obtained positive electrode active material was evaluated as follows.
[0099] (a) Evaluation of composition The composition of the positive electrode active material was analyzed by ICP emission spectrometry. The evaluation results are shown in the "Composition" column of Table 1.
[0100] (b) Nickel occupancy rate of the lithium site (3b) About 2 g of the positive electrode active material prepared in the following Examples and Comparative Examples was filled into a vanadium tube, which was then completely sealed. Neutron diffraction measurements were then performed at BL20 (iMATERIA, Ibaraki Prefecture) at the Japan Proton Accelerator Research Complex (J-PARC) under conditions that yielded an intensity of 10,000 cps or more in double frame mode.
[0101] The neutron diffraction pattern obtained from the rear detector bank was subjected to Rietveld analysis using the analysis software Z-Code. In this analysis, the space group was set to R-3m, with lithium and mixed nickel (nickel in the lithium site) set as chemical species at the 3b site, and nickel and element M set as chemical species at the 3a site. After refining the scale factor, lattice constant, and global parameters, the site occupancy rate and atomic coordinates were refined. The atomic displacement parameters for lithium were: 0.9 to 1.0 Å. 2 , Nickel and element M: 0.3-0.5Å 2 , Oxygen: 0.6~0.8Å 2 After refining the site occupancy and atomic coordinates, the reliability parameter S value was deemed to have converged at 3.0 or less. The nickel site occupancy of the obtained lithium site (3b site) was calculated, and the results are shown in the "Ni occupancy of 3b site" column in Table 1.
[0102] In addition, the S value, which is a reliability parameter when performing Rietveld analysis, is shown in the "S value" column of Table 1.
[0103] Powder neutron diffraction measurements can also be performed using a High Resolution Powder Diffractometer (HRPD) installed in the Japan Atomic Energy Agency's JRR-3 reactor or the Super HRPD at J-PARC.
[0104] (c) (003) plane peak half-width X-ray diffraction patterns were measured using an XRD diffractometer (PANalytical, X'Pert PRO) with Cu-Kα radiation as an X-ray source. From the obtained X-ray diffraction patterns, the half-width, which is the width of the profile at half the maximum intensity value, was calculated for the diffraction peak of the (003) plane of the hexagonal layered structure. The sample was filled in the groove of a circular glass holder with an outer diameter of 32 mmφ (flat sample holder, inner diameter 24 mmφ, groove depth 0.5 mm, PANalytical product number 9200 540 12391) and fixed to a specified sample holder (PANalytical product number 9430 018 13321) for measurement. The XRD diffractometer used was equipped with a Bragg-Brentano optical system.
[0105] The evaluation results are shown in the column "(003) half width" in Table 1.
[0106] From the obtained X-ray diffraction patterns, it was confirmed that the positive electrode active materials produced in the following Examples and Comparative Examples were made of lithium nickel composite oxide, and that the lithium nickel composite oxide had a hexagonal layered structure.
[0107] (d) Average primary particle diameter In the SEM observation image of the lithium nickel composite oxide particles, 15 secondary particles that could be observed in their entirety were selected by image analysis, and primary particles were selected from each selected secondary particle. At this time, a total of 30 primary particles were selected. The major axis lengths of the selected primary particles were then measured, and the average value was taken as the average primary particle diameter. The evaluation results are shown in the "Average primary particle diameter" column in Table 1.
[0108] (e) Median diameter (D50) The volumetric particle size distribution was measured using a laser diffraction scattering type particle size analyzer (Microtrack HRA, manufactured by Nikkiso Co., Ltd.), and the median diameter was calculated from the particle size distribution.
[0109] The evaluation results are shown in the "D50" column of Table 1.
[0110] (f) Number ratio of single primary particles The lithium nickel composite oxide particles were embedded in a thermosetting resin and then polished with a cross-section polisher (SM-09010, manufactured by JEOL Ltd.). The cross-sections of the obtained particles were observed with a Schottky field emission scanning electron microscope (Ultra 55, manufactured by Carl Zeiss), and the number ratio of single primary particles was evaluated from 100 particles. (Secondary battery production and evaluation) (a) Evaluation of charge capacity, discharge capacity, and coulombic efficiency (a-1) Preparation of coin-type battery The positive electrode active materials prepared in the following Examples and Comparative Examples were used to prepare coin-type batteries as shown in FIG.
[0111] As shown in FIG. 2, the coin battery CBA is composed of a case CA and electrodes housed within this case CA.
[0112] The case CA has a positive electrode can PC that is hollow and has one open end, and a negative electrode can NC that is placed in the opening of the positive electrode can PC, and is configured so that when the negative electrode can NC is placed in the opening of the positive electrode can PC, a space for accommodating an electrode is formed between the negative electrode can NC and the positive electrode can PC.
[0113] The electrodes consist of a positive electrode PE, a separator SE1, and a negative electrode NE, which are stacked in this order and are housed in a case CA so that the positive electrode PE contacts the inner surface of a positive electrode can PC and the negative electrode NE contacts the inner surface of a negative electrode can NC via a wave washer WW.
[0114] The case CA is provided with a gasket GA, which restricts relative movement between the positive can PC and the negative can NC so as to maintain a non-contact state, i.e., an electrically insulated state, and also has the function of sealing the gap between the positive can PC and the negative can NC to provide an airtight and liquid-tight barrier between the inside of the case CA and the outside.
[0115] This coin-type battery CBA was fabricated as follows. First, 52.5 mg of the positive electrode active material obtained in each Example and Comparative Example, 15 mg of acetylene black, and 7.5 mg of polytetrafluoroethylene (PTFE) resin were mixed. The resulting mixture was then thinned to a diameter of 11 mm and a weight of about 75 mg to fabricate a positive electrode PE, which was then dried in a vacuum dryer at 100°C for 12 hours.
[0116] Using the prepared positive electrode PE, negative electrode NE, separator SE1, and electrolyte, a coin-type battery CBA was produced in a glove box in an Ar atmosphere with a dew point controlled at -60°C.
[0117] For the negative electrode NE, lithium metal punched into a disk shape with a diameter of 13 mm was used.
[0118] The separator SE1 was a polyethylene porous film with a thickness of 25 μm. The electrolyte used was a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1, with 1M LiClO4 as the supporting electrolyte (manufactured by Toyama Pharmaceutical Co., Ltd.).
[0119] (a-2) Evaluation of charge capacity, discharge capacity, and efficiency After the coin cell CBA was made, it was left for about 12 hours. After the open circuit voltage OCV stabilized, the current density to the positive electrode was increased to 0.1 mA / cm. 2The capacity when the battery was charged to a cut-off voltage of 4.3 V was taken as the charge capacity. After charging, the battery was left to rest for 1 hour, and then the capacity when the battery was discharged to a cut-off voltage of 2.5 V was taken as the discharge capacity. Furthermore, the coulombic efficiency, which is the ratio of the discharge capacity to the charge capacity, was calculated.
[0120] (b) Cycle characteristics (b-1) Preparation of laminated battery Using the positive electrode active materials prepared in the following Examples and Comparative Examples, laminate type batteries shown in FIG. 3 were prepared.
[0121] As shown in Fig. 3, the laminated battery LBA has a structure in which a laminate of a positive electrode film PS, a separator SE2, and a negative electrode film NS is impregnated with an electrolyte and sealed with a laminate LA. A positive electrode tab PT is connected to the positive electrode film PS, and a negative electrode tab NT is connected to the negative electrode film NS, and the positive electrode tab PT and the negative electrode tab NT are exposed to the outside of the laminate LA.
[0122] This laminated battery LBA was fabricated as follows: 20.0 g of the obtained positive electrode active material, 2.35 g of acetylene black, and 1.18 g of polyvinylidene fluoride were dispersed in N-methyl-2-pyrrolidone (NMP) to form a slurry. 2 The positive electrode active material was applied so that 7.0 mg of the positive electrode active material was present per unit area. Next, the slurry containing the positive electrode active material was applied to the Al foil, and the slurry was dried in the air at 120 ° C for 30 minutes to remove the NMP. The Al foil to which the positive electrode active material was applied was cut into a strip of 66 mm in width and roll pressed with a load of 1.2 t to prepare a positive electrode film. The positive electrode film was then cut into a rectangle of 50 mm × 30 mm, and dried in a vacuum dryer at 120 ° C for 12 hours to be used as the positive electrode film PS of the laminated battery LBA.
[0123] In addition, a negative electrode film NS was prepared by applying a negative electrode composite paste, which is a mixture of graphite powder with an average particle size of about 20 μm and polyvinylidene fluoride, to a copper foil. A polyethylene porous film with a thickness of 20 μm was used for the separator SE2, and a 3:7 mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1M LiPF6 as the supporting electrolyte (manufactured by Ube Industries, Ltd.) was used for the electrolyte.
[0124] In a dry room controlled at a dew point of -60°C, the laminate of the positive electrode film PS, separator SE2, and negative electrode film NS was impregnated with an electrolyte and sealed with a laminate LA to prepare a laminate type battery LBA.
[0125] (b-2) Cycle characteristics The cycle characteristics were evaluated by measuring the capacity retention rate after 500 charge / discharge cycles. Specifically, the laminated battery LBA was first placed in a thermostatic chamber maintained at 25°C and charged at a current density of 0.3 mA / cm. 2 The battery was conditioned by repeating five cycles of charging to a cut-off voltage of 4.2 V, resting for 10 minutes, and discharging to a cut-off voltage of 2.5 V. The battery was then placed in a thermostatic chamber maintained at 45°C, and discharged at a current density of 2.0 mA / cm 2 The battery was charged to a cut-off voltage of 4.2 V, and after a 10-minute break, discharged to a cut-off voltage of 2.5 V. This cycle was repeated 500 times. The capacity retention rate, which is the ratio of the discharge capacity at the 500th cycle after conditioning to the discharge capacity at the first cycle, was calculated and evaluated. The discharge capacity at the first cycle and the capacity retention rate are shown in the "Initial discharge capacity" and "Capacity retention rate" columns of "Cycle characteristics" in Table 1, respectively. (Production conditions of positive electrode active material) [Example 1] A nickel composite oxide (D50 particle size: 5.2 μm) obtained by a known method and having a substance ratio of nickel and cobalt of Ni:Co=95.0:5.0 was mixed with lithium hydroxide to prepare a raw material mixture (mixing step).
[0126] In the mixing step, the nickel composite oxide and lithium hydroxide were thoroughly mixed using a shaker mixer (Willi & Bachofen (WAB), model: TURBULA Type T2C) to prepare a raw material mixture.
[0127] In the mixing process, the raw materials were weighed and mixed so that the ratio of the amount of lithium (Li) contained in the raw material mixture to the amount of nickel and cobalt (Me) other than lithium, Li / Me, was 0.92. The nickel composite oxide was obtained by heat-treating the nickel composite hydroxide obtained by the crystallization method.
[0128] This raw material mixture was fired in an oxygen-containing atmosphere with an oxygen concentration of 90% by volume, the remainder being nitrogen (firing step). The oxygen concentration in the oxygen-containing atmosphere in the firing step is shown in the "oxygen concentration" column of Table 1. In the first firing step, the firing temperature was raised to 500°C, which was the first firing temperature, and held at 500°C, which was the first firing temperature, for 7 hours. After the first firing step, the second firing step was subsequently carried out. In the second firing step, the temperature was raised to 700°C, which was the second firing temperature, and firing was performed by holding at 700°C, which was the second firing temperature, for 12 hours.
[0129] The fired lithium nickel composite oxide was crushed (crushing step) to obtain a positive electrode active material made of lithium nickel composite oxide particles.
[0130] Observation of the obtained positive electrode active material by SEM confirmed that the lithium nickel composite oxide particles had an average primary particle diameter of 0.63 μm and were composed of secondary particles made of the primary particles. That is, the number ratio of a single primary particle was 0. The number ratio of a single primary particle was also 0 in the following other examples.
[0131] Other evaluation results are shown in Table 1.
[0132] The positive electrode active material thus obtained was used to fabricate the coin-type battery and laminate-type battery described above, and the evaluation results were shown in Table 1. [Example 2] The mixing ratio of lithium hydroxide and nickel composite oxide was changed so that the Li / Me ratio of the raw material mixture in the mixing step was the value shown in the "Charged Li / Me ratio" column in Table 1. The holding time at the first firing temperature in the first firing step was set to the conditions shown in Table 1. A positive electrode active material, a coin-type battery, and a laminate-type battery were produced and evaluated under the same conditions as in Example 1, except for the above points. The evaluation results are shown in Table 1.
[0133] Fig. 4 shows the powder neutron diffraction pattern (Observed) of the lithium nickel composite oxide measured in Example 2. Fig. 4 also shows the simulation pattern (Calculated) obtained by Rietveld analysis, the difference (Difference) between the measured powder neutron diffraction pattern and the simulation pattern, and the Bragg positions (Bragg Positions). [Examples 3 and 4] In the mixing step, a nickel composite oxide having a substance ratio of nickel, manganese, and cobalt of Ni:Mn:Co=92.0:3.0:5.0 was used as the nickel composite oxide. The mixing ratio of lithium hydroxide and the nickel composite oxide was selected so that the Li / Me ratio of the raw material mixture was the value shown in the "Feed Li / Me ratio" column in Table 1.
[0134] In the firing step, the holding time at the first firing temperature in the first firing step and the second firing temperature in the second firing step were set to the conditions shown in Table 1. Except for the above, a positive electrode active material, a coin-type battery, and a laminate-type battery were produced and evaluated under the same conditions as in Example 1. The evaluation results are shown in Table 1. [Comparative Example 1] In the mixing step, the mixing ratio of lithium hydroxide and nickel composite oxide was changed so that the Li / Me ratio of the raw material mixture was the value shown in the "Charged Li / Me ratio" column in Table 1. Except for the above, a positive electrode active material, a coin-type battery, and a laminate-type battery were produced and evaluated under the same conditions as in Example 2. The evaluation results are shown in Table 1. [Comparative Example 2] Pure water at 20°C was added to the positive electrode active material obtained in Comparative Example 1 to prepare a slurry containing 1250 g of the positive electrode active material per 1 L of water (slurrying step). Next, the slurry was stirred for 20 minutes, passed through a filter press, and dehydrated to prepare a washed cake (solid-liquid separation step). Note that water with an electrical conductivity of 1 μS / cm or less was used as the pure water.
[0135] The obtained washed cake was dried at 190° C. for 10 hours in a vacuum atmosphere to obtain a positive electrode active material of Comparative Example 2 (drying step).
[0136] The obtained positive electrode active material was evaluated as described above. The evaluation results are shown in Table 1. In addition, coin type batteries and laminate type batteries were produced and evaluated in the same manner as in Example 1, except that the obtained positive electrode active material was used. The evaluation results are shown in Table 1. [Comparative Example 3] In the mixing step, the mixing ratio of lithium hydroxide and nickel composite oxide was changed so that the Li / Me ratio of the raw material mixture was the value shown in the "Charged Li / Me ratio" column in Table 1. Except for the above, a positive electrode active material, a coin-type battery, and a laminate-type battery were produced and evaluated under the same conditions as in Example 4. The evaluation results are shown in Table 1.
[0137] [Table 1] (Evaluation Results) According to the results shown in Table 1, it was confirmed that the positive electrode active materials of Examples 1 and 2, in which the occupancy rate of nickel present in the lithium site (3b site) is 2.5% or more and 10.0% or less, have improved cycle characteristics compared to Comparative Examples 1 and 2, in which the contents of nickel and element M are the same.
[0138] The same was also confirmed by comparing Examples 3 and 4 with Comparative Example 3. [Explanation of symbols]
[0139] CBA coin cell battery PE positive electrode NE negative electrode SE1 Separator GA Gasket WW Wave Washer CA Case PC positive electrode can NC negative electrode can LBA Laminated Battery PS positive electrode sheet NS negative electrode sheet SE2 Separator LA Laminate PT Positive tab NT negative electrode tab
Claims
1. A positive electrode active material for a lithium ion secondary battery, comprising a lithium nickel composite oxide having a hexagonal layered structure, The lithium nickel composite oxide contains lithium (Li), nickel (Ni), and an element M (M) in a ratio of substance amounts of Li:Ni:M=a:b:c (wherein 0.90≦a<1.00, 0.80≦b<1.00, 0.00<c≦0.20, b+c=1, and the element M is at least one element selected from the group consisting of Mn, Co, Al, Ti, Zr, W, Fe, Si, Nb, Mg, Ca, B, Na, K, Mo, Cu, V, P, and Ba), A positive electrode active material for a lithium ion secondary battery, in which an occupancy rate of nickel present in lithium sites (3b sites) is 2.5% or more and 10.0% or less, obtained by analyzing a powder neutron diffraction pattern of the lithium nickel composite oxide by the Rietveld method.
2. 2. The positive electrode active material for lithium ion secondary batteries according to claim 1, wherein the half-width of the diffraction peak of the (003) plane in the powder X-ray diffraction pattern of the lithium nickel composite oxide measured using Cu-Kα radiation as an X-ray source is 0.074° or more and 0.125° or less.
3. 3. The positive electrode active material for a lithium ion secondary battery according to claim 1, wherein the average primary particle size of the lithium nickel composite oxide is 0.05 μm or more and 1.0 μm or less.
4. 3. The positive electrode active material for a lithium ion secondary battery according to claim 1, wherein a median diameter in a volume-based particle size distribution measured by a laser diffraction / scattering method is 0.1 μm or more and 20.0 μm or less.
5. The battery includes at least a positive electrode, a negative electrode, and a non-aqueous electrolyte; A lithium ion secondary battery, wherein the positive electrode comprises the positive electrode active material for lithium ion secondary batteries according to claim 1 or 2.
Citation Information
Patent Citations
Lithium transition metal oxide compound for lithium secondary battery positive electrode active material, its manufacturing method and secondary battery using it
JP2001243949A
Cathode active substance for nonaqueous secondary battery and cathode
JP2004355824A
Method for manufacturing positive electrode active material for nonaqueous electrolyte secondary battery
JP2017188444A
Positive electrode active material for nonaqueous electrolyte secondary battery
JP2017188445A
Nonaqueous electrolyte secondary battery
WO2017169129A1